LIONEL MESSI - Adamson, Thomas K., 1970-; Downs, Kieran (Minneapolis, Minnesota : Bellwether Media, Inc., 2024)
"Engaging images accompany information about Lionel Messi. The combination of high-interest subject matter and light text is intended for students in grades 3 through 7"
Index
Includes index
Includes bibliographical references (page 23) and index.
Ages 7-12
Grades 4-6
Keywords: Messi, Lionel, -- 1987- -- Juvenile literature; Soccer players -- Argentina -- Biography -- Juvenile literature; Argentina. -- Soccer players